2021
DOI: 10.1038/s41467-021-25730-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac radiotherapy induces electrical conduction reprogramming in the absence of transmural fibrosis

Abstract: Cardiac radiotherapy (RT) may be effective in treating heart failure (HF) patients with refractory ventricular tachycardia (VT). The previously proposed mechanism of radiation-induced fibrosis does not explain the rapidity and magnitude with which VT reduction occurs clinically. Here, we demonstrate in hearts from RT patients that radiation does not achieve transmural fibrosis within the timeframe of VT reduction. Electrophysiologic assessment of irradiated murine hearts reveals a persistent supraphysiologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
90
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 71 publications
2
90
1
6
Order By: Relevance
“…SBRT is an emerging therapeutic option for patients with refractory VA [ 5 ]. Although the mechanism of suppressing VA is not fully elucidated, recent researches have suggested possible mechanisms [ 13 , 14 , 15 ]. Radiotherapy-induced fibrotic remodeling and increased CV are presumed to prevent re-entry of cardiac impulses [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SBRT is an emerging therapeutic option for patients with refractory VA [ 5 ]. Although the mechanism of suppressing VA is not fully elucidated, recent researches have suggested possible mechanisms [ 13 , 14 , 15 ]. Radiotherapy-induced fibrotic remodeling and increased CV are presumed to prevent re-entry of cardiac impulses [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of suppressing VA is not fully elucidated, recent researches have suggested possible mechanisms [ 13 , 14 , 15 ]. Radiotherapy-induced fibrotic remodeling and increased CV are presumed to prevent re-entry of cardiac impulses [ 13 , 14 , 15 ]. However, conducted studies have observed changes over days to months [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 However, any perturbation of myocardial conduction whether increase or decrease may be sufficient to prevent re-entrant VT and most recent data again points to a 'supraphysiologic' phenotype induced by radiation. 35 The acute and late side effects of radiotherapy also need consideration, including those affecting the heart itself. We did not perform follow-up imaging apart from echo and did not document any clinically significant acute side effects, but long-term effects including pericardial fibrosis and constriction, or coronary and valve disease are well-documented in cancer survivors and are a concern.…”
Section: Discussionmentioning
confidence: 99%